Implementation of the Madrasah Digital Reporting Application (RDM) in Reporting Evaluation of Learning Outcomes at Madrasah Ibtidaiyah Sabilal Muhtadin Maroangin in Puncak Village, Sinjai Selatan District - Syamsiah Hasyim; Sitti Fatimah; Usnidah Umar; Susi , Susi (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to explore the implementation of the Madrasah Digital Report Card Application (RDM) in evaluating learning outcomes at Madrasah Ibtidaiyah Sabilal Muhtadin Maroangin, Puncak Village, South Sinjai District. Qualitative descriptive method was used with data collection techniques through observation, interviews, and documentation. Data were analyzed by data reduction, data presentation, and conclusion drawing. The results showed that the implementation of RDM provides convenience in evaluating learning outcomes, including filling in grades, archiving, and printing student grades. Assessment indicators show that RDM in the madrasah is in accordance with existing guidelines and SOPs, with good planning preparation, efficient assessment implementation by educators, and effective digital reporting. This research is expected to increase understanding of the implementation of RDM in the context of madrasah education.